2022
DOI: 10.6007/ijarbss/v12-i10/14751
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Customer Satisfaction on Shopee

Abstract: There are several elements that have a direct impact on the level of enjoyment that consumers derive from online shopping. Consequently, the purpose of the present study was to investigate the personal experiences of Shopee users and the elements that influence their degree of satisfaction. The result of this study is expectantly to allow Shopee to strengthen their business policy and practices on how they can provide better service to the customer. A total of 162 Shopee customers who met the study's eligibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…Interestingly, the research findings diverge from those of previous studies that highlighted the significant influence of perceived convenience on customers' online shopping behavior, as demonstrated by Yo et al (2021), Shanthi & Desti (2015), Ching et al (2021), andMustakim et al (2022). This discrepancy prompts further examination into the potential reasons behind the observed differences.…”
Section: Discussioncontrasting
confidence: 82%
“…Interestingly, the research findings diverge from those of previous studies that highlighted the significant influence of perceived convenience on customers' online shopping behavior, as demonstrated by Yo et al (2021), Shanthi & Desti (2015), Ching et al (2021), andMustakim et al (2022). This discrepancy prompts further examination into the potential reasons behind the observed differences.…”
Section: Discussioncontrasting
confidence: 82%
“…For the questionnaire items, five items were changed from each of the related research. Refer to Appendix A in regard to the accuracy of delivery [58,59], price of delivery [60,61], information quality [45,62,63], ease of payment [58,59,64], payment security [65,66] and customer satisfaction [36,67] with brand loyalty items [68][69][70].…”
Section: Development Of Measurement Scalesmentioning
confidence: 99%
“…As customers spend fairly time shopping and extra time engaged in other activities, their need for convenience has grown. Consequently, they increasingly prioritize and prefer online purchases over visits to physical stores (Mustakim, Hassan, Sauid, Ebrahim & Mokhtar, 2022). Online shopping on Shopee Malaysia builds a convenient environment for customers.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived usefulness is essential in affecting consumer behavior (Koch et al, 2020). Based on Mustakim et al (2022), perceived usefulness has a strong impact on customer satisfaction in Shopee Malaysia. However, our research showed a different result on the relationship between perceived usefulness towards customer satisfaction in Shopee Malaysia.…”
Section: Discussionmentioning
confidence: 99%